2021
DOI: 10.1002/hbm.25601
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical psychotic‐like experiences and schizotypy dimensions: Associations with hippocampal subfield and amygdala volumes

Abstract: Schizotypy and psychotic-like experiences (PLE) form part of the wider psychosis continuum and may have brain structural correlates in nonclinical cohorts. This study aimed to compare the effects of differential schizotypy dimensions, PLE, and their interaction on hippocampal subfields and amygdala volumes in the absence of clinical psychopathology. In a cohort of 367 psychiatrically healthy individuals, we assessed schizotypal traits using the Oxford-Liverpool Inventory of Life Experiences (O-LIFE) and PLE us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…These findings may suggest compensation across mechanisms associated with ASD and SSD. We reason that this compensatory mechanism is plausible, given previous studies reporting that ASD was associated with increased volume [ 83 , 84 ] and SSD with reduced volume [ 20 , 85 , 86 ]. Collectively, the co-occurrence of ASD and SSD may yield effects that are protective of normative brain structures, which mirrors previously observed effects of ASD and SSD on brain and social functioning [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These findings may suggest compensation across mechanisms associated with ASD and SSD. We reason that this compensatory mechanism is plausible, given previous studies reporting that ASD was associated with increased volume [ 83 , 84 ] and SSD with reduced volume [ 20 , 85 , 86 ]. Collectively, the co-occurrence of ASD and SSD may yield effects that are protective of normative brain structures, which mirrors previously observed effects of ASD and SSD on brain and social functioning [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 91%
“…This indicates at least two dissociations, i.e., by hippocampal region as well as for structure (volumes) vs. function (rCBF). Indeed, recent association studies for schizotypy have failed to identify correlations with total hippocampal volume per se [ 92 ], while subfield analyses do report effects on particular subregions related to subclinical psychotic-like features [ 20 ]. Moreover, studies have found increased [ 83 , 84 ], decreased [ 93 ] and no association [ 94 , 95 ] of hippocampal volumes with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation